(untitled) - Feldman, Robert S. (New York, 2011)
P.O.W.E.R. Learning is the only first-year experience text with a unifying system for critical thinking and problem solving. P.O.W.E.R. Learning maximizes students' potential for success in college and in life. Using the scientifically-based, yet simple and class-tested principles of the P.O.W.E.R (Prepare, Organize, Work, Evaluate, and Rethink) system, students gain a sense of mastery and achievement as they move through the text; with the growth of their confidence comes the increased intellectual enthusiasm and personal discipline needed for them to excel.
Keywords: College student orientation,Life skills,Định hướng sinh viên đại học,Kỹ năng sống